Students' Perceptions In Using YouTube to Improve Young Learners' Vocabulary Viewed Islamic English Content - Liza Hidayati; Syafryadin Syafryadin (Edu-Ling: Journal of English Education and Linguistics, 2023)
The objective of this research is to described the students’ perception in using YouTube to improve young learners’ vocabulary viewed Islamic English content. The sample of this research were fourth- grade students at Islamic elementary school of IQRA 2. In this study, a quantitative approach was used with a descriptive research design. The data were gathered by using a closed-ended questionnaire, the researchers in this study gathered data on what are students what are students’ perception in using YouTube to improve young learners’ vocabulary viewed Islamic English content. Furthermore, the descriptive statistics were used to analyzed the data, and the results were presented and explained in tables. The finding showed the most students strongly agree with the statement, the use of YouTube improved students’ vocabulary viewed Islamic English content. In conclusion, Students given the positive perceptions towards the use of YouTube improved students’ English vocabulary in teaching and learning process. Keywords: Students’ perception, YouTube, Learners’ Vocabulary, Islamic English Content